Novel tool for the study of cholecystokinin-stimulated pancreatic enzyme secretion. - Gaisano, H Y (1989)
The molecular events that mediate cholecystokinin (CCK)-stimulated pancreatic secretion are not well defined because of the complex receptor-binding and concentration-response characteristics of this hormone. Functional models of receptor occupancy initiating the cascade leading to secretion have been complicated by the inhibition of secretion effected by supramaximal concentrations of CCK. Recent report of a CCK analogue that does not exhibit supramaximal inhibition led us to synthesize a similar analogue that could also be radiolabeled for studies of receptor binding and affinity labeling, and for studies of second messenger activity. This probe, D-Tyr-Gly-[(Nle28,31)CCK-26-32]-phenethyl ester, was a fully efficacious secretagogue with no supramaximal inhibition, and, unlike native hormone, bound to a single class of sites present on both acini and membranes. Occupation of this site correlated well with stimulation of secretion. Evidence that this was indeed a CCK-binding site were the abilities of CCK and the antagonist L-364, 718 to inhibit binding of this analogue. Affinity labeling confirmed the identity of the site mediating secretory stimulation as a Mr = 85,000-95,000 protein. Whereas the nonhydrolyzable guanosine triphosphate analogue, 5'-guanylyl-imidodiphosphate, was a potent inhibitor of CCK binding, it had no effect on binding of this secretagogue, suggesting that a novel cascade not involving a guanine nucleotide-binding protein mediates CCK stimulation of pancreatic secretion.